Heat-killed Enterococcus fecalis (EC-12) supplement alters the expression of neurotransmitter receptor genes in the prefrontal cortex and alleviates anxiety-like behavior in mice. (16th February 2020) - Kambe, Jun; Watcharin, Sovijit; Makioka-Itaya, Yuko; Inoue, Ryo; Watanabe, Gen; Yamaguchi, Hirohito; Nagaoka, Kentaro
Highlights: Gut microbiota promotes mental health by combating depression and anxiety. EC-12 supplementation exhibited an anti-depressive trend in mice. EC-12 supplement significantly enhances the expression of Adrb3, Avpr1a, and Drd5. EC-12 supplement enhances Butyricicoccus and Enterococcus in the gut. Heat-killed EC-12, a novel probiotic to promote mental health. Abstract: Gut microbiota plays a crucial role in the maintenance of mental health and influences mental disorders such as depression and anxiety. Several studies have reported the beneficial affects of probiotics in mental health. Heat-killed Enterococcus faecalis strain EC-12 (EC-12), a lactic acid bacterium induces activation of the immune system. However, little is known about the effect of EC-12 on mental health. In the present study, the anti-anxiety effect of EC-12 was elucidated in vivo . Male mice fed on diet supplemented with EC-12 showed decreased anxiety-like behavior in open-field and elevated plus-mazetest. In addition, EC-12 supplementation exhibited an anti-depressive trend in mice subjected to forced swim test. The expression of neurotransmitter receptor genes: Adrb3 and Avpr1a were significantly enhanced in EC-12 supplemented mice compared to that of the control mice. In mice, analyses of gut microbiota composition by next generation sequencing revealed significant increase in Butyricicoccus and Enterococcus with EC-12 supplementation. Significant difference was not detected in the expression of neurotransmitter receptor genes in the prefrontal cortex with the administration of sodium butyrate compared to that of the control group. The mechanism associated with EC-12 mediated reduced anxiety-like behavior and altered gene expression in the brain needs to be further elucidated. Taken together, the present study is the first to report the possibility of exploiting the anti-anxiety effect of heat-killed EC-12 as a novel probiotic to promote mental health.